The Effect of Religious Music Therapy on Reducing the Degree of Menstrual Pain in Adolescent Girls - Rahmat, Rahmat Kurniawan; Dhia Diana Fitriani, Dhia; Putri Wulandari, Putri; Nurmiaty; Faisal, T. Iskandar; Khaira, Nuswatul (Caring : Jurnal Keperawatan, 2025)
Human growth and development into adulthood undergo a stage called puberty. One of the signs that a woman has entered the age of puberty is the occurrence of menstruation. One of the disorders that occur during menstruation is dysmenorrhea. Dysmenorrhea is pain or during menstruation, this is one of the most common gynecological problems in adolescent girls. Behavior in dealing with dysmenorrhea pain in adolescents can be done in a non-pharmacological way, namely religious music therapy. When listening to music, our brain will automatically produce a certain amount of serotonin. so that we can feel calm and divert attention. The purpose of this study was to determine the effect of religious music therapy on decreasing the degree of menstrual pain in adolescent girls in RT 09 kp. New Mekar kab. Tangerang. Research method The type of research used in this study is a quasi-experimental (quasi-experimental) research design with a one group comparison pretest-posttest design, data collection instruments using NRS pain measurement questionnaires and music therapy SOPs. The population in this study were young women in RT 09 Kp. Mekar Baru Kab. Tangerang amounted to 50 young women with a total sample of 15 young women. The technique used is purposive sampling technique. Data analysis using Wilcoxon test, based on data analysis with Wilcoxon test with a significance degree of p <0.05 (5%). The results of the statistical test obtained a value (pvalue = 0.001), so it can be concluded that there is an effect of giving religious music therapy on decreasing the degree of menstrual pain in adolescent girls in RT 09 Kp. Mekar Baru Kab. Tangerang. Suggestions from the results of this study are expected for respondents who experience menstrual pain, to do religious music therapy as an alternative way by using non-pharmacological therapy for pain reduction because it is very easy to do alone.